Práticas de promoção da saúde no contexto do SUS : mapeando significados junto a usuários em uma UBS capixaba - Roberto, Moises da Silva (2016)
Health promotion is linked to the diversity of services developed in practice. It is a strategic element in the search for the most promising care practices, contributing to the consolidation of the Unified Health System (Sistema Único de Saúde - SUS) while Public Policy. However, the health promotion has been variously described in the literature. In this sense, it considered necessary to perform a review of health promotion and its implications for health practice, without pretending to ex st t e “st te f t e t”. This study aimed to carry out a descriptive-analytic study of daily practices in the perspective of expanded clinic in a Health Promotion Group, the Group of Men, developed in a basic health Unit Capixaba. The investigative paths passed through the assumptions of qualitative research, taking the daily activities of Group of Men as a methodological perspective and adding ethnographic to describe, analyze, understand and discuss health promotion practices developed in the daily life of this group, and its practical implications in health care in light of the expanded clinic, seeking to identify the progress and challenges, and understand the context of production practices and participation of users. In the description and analysis of data, it was established three categories in relation to health promotion practices developed in Group of Men: a) communication space: analyzes the Group of Men in the view of dialogue, listening and expression of participants in the Group of Men, seeking to identify whether the subjects are open to speaking l ste bey t e “ ec c l” conversation that aims to collect only symptoms of specific pathologies (traditional anamnesis); b) development of bond: analyzes the space of Group of Men with respect to the relationship between individuals (between users and health staff), in order to verify if the relationship is close or whether it is formal and bureaucratic, pointing out the advantages of bond formation for health care and the challenges for achieving the Group of Men; c) leadership: analyzes the behavior, attitude and participation of users, identifying whether they e c s e e ct s “s bject” or autonomy holders are see ct e ely s “p t e ts”, that is, passive and unable people to contribute to health care, should, in this case, submit to the technical and scientific knowledge that health professionals monopolize, a superior list of professionals in relation to users. Finally, it points out the challenges to develop the role of participants in the Group of Men.